Analyses of the concepts of genotype and phenotype in course books from 1950 to nowadays (Research, Society and Development, 2020)
With the progresses made in the field of genetics in interactions with other areas of research such as physiology, behavior analyses, among others, the concepts of genotype and phenotype are in constant transformation. The goal of this research was to highlight how the concepts of genotype and phenotype were presented in biology textbooks from 1950 to 2013. To do so, we proceeded an analyses of contends, bases upon categorization, from the decade of 1950 to the year of 2013. The concepts were analyzed taking in account the epoch in which the course books were edited. This research justifies itself by the need of evaluating the concepts presented in course books. The results show us that the concepts of genotype and phenotype presented in the course books did not follow the understanding of them by the scientific community of each epoch. There were evidences that generally occurs a longing of time between the didactic transposition of the contends and the scientific knowledge development. One can understand that part of this lack of time is acceptable once it is very difficult to edict course books as fast as or immediately as the scientific researches are developed. However authors and editors must be aware of the need to update such concepts and take care about letting decades of distance between the presented concepts in course books and their real and acceptable understanding by the scientific community.